Quantitative Analysis of Foreign Trade and Environmental Efficiency in China. Issue 7 (2nd July 2016) - Song, Malin; Zhou, Yuanxiang
ABSTRACT: This article analyzes the relationships among trade, the economy, and environmental quality in China. First, in the context of these relationships, the Super-SBM model is used to calculate the environmental efficiencies of thirty Chinese provinces and cities to obtain the degrees of regional disparity. Second, China's provincial panel data from 2003 and 2012 are used to establish an influential factor indicator system of environmental efficiency. A section-weighted fixed effect model then provides insights about influential factors such as spatial heterogeneity. Third, the article establishes a variable coefficient model to identify the relationships among the objects of the study and divides the Chinese regions into four types. The suggestions include enhancing environmental and business regulations to ensure equilibrium between trade, the environment, and local economies.